2021
DOI: 10.1186/s13023-021-02009-7
|View full text |Cite
|
Sign up to set email alerts
|

Pilot investigation of circulating angiogenic and inflammatory biomarkers associated with vascular malformations

Abstract: Background Vascular malformations in the central nervous system are difficult to monitor and treat due to their inaccessible location. Angiogenic and inflammatory proteins are secreted into the bloodstream and may serve as useful biomarkers for identifying patients at risk for complications or with certain disease phenotypes. Methods A validated multiplex protein array consisting of 26 angiogenic and inflammatory biomarkers (Angiome) was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…For instance, levels of ANG2 skewed higher in brain and lung AVMs but were reduced in liver AVMs when combined HHT patient data was analyzed, though this was not statistically significant or separated between the types of HHT. 72 When comparing ANG2 levels in heterozygous HHT models, pulmonary ANG2 was found to be unchanged in Eng +/− mice but increased in the lungs of Alk1 +/− mice compared to corresponding controls. 70 These studies are relevant because incidences of tissue/organ-specific AVMs differ between the various types of HHT.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, levels of ANG2 skewed higher in brain and lung AVMs but were reduced in liver AVMs when combined HHT patient data was analyzed, though this was not statistically significant or separated between the types of HHT. 72 When comparing ANG2 levels in heterozygous HHT models, pulmonary ANG2 was found to be unchanged in Eng +/− mice but increased in the lungs of Alk1 +/− mice compared to corresponding controls. 70 These studies are relevant because incidences of tissue/organ-specific AVMs differ between the various types of HHT.…”
Section: Discussionmentioning
confidence: 97%
“…71 Recently, combined measurements of circulating ANG2 from patients with the 3 major forms of HHT, although not statistically significant, trended toward a decrease in ANG2 levels. 72 Furthermore, cultured blood outgrowth ECs from ENG -HHT1 and ALK1 -HHT2 patients and several tissues from Eng +/− heterozygous mutant mice exhibited substantial decreases in ANG2 expression. 70,73 Taking these discrepancies into consideration, several explanations could account for these observed variances.…”
Section: Discussionmentioning
confidence: 97%
“…On T-helper lymphocytes, CXCR4 under-expression seems to be a central phenomenon in the idiopathic CD4 lymphopenia [ 29 ], but the infectious profiles are quite different. An alternative explanation could be a chronic elevation of the CXCL12 plasma level, described in severe infection [ 30 , 31 ] and recently in HHT [ 32 ]. Such an elevation is known to lead to continuous CXCR4 and CD26 internalization as a desensitization process [ 9 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Administration of Angpt2 monoclonal antibodies prevented and resolved retinal AVMs of Smad4 mutant mice [104] and improved brain vascular morphology in other HHT models [105]. However, other studies showed that the blood ANGPT2 levels were decreased in HHT2 patients and unchanged in HHT1 patients [106,107]. Further, cultured blood outgrowth ECs from HHT1 and HHT2 patients, along with several tissues collected from Eng +/− mice exhibited substantial decreases in Angpt2 levels [108,109].…”
Section: Angiopoetin-2 (Angpt2) Antibodiesmentioning
confidence: 99%